A CRITICAL ANALYSIS OF THE ROLE OF SOCIAL SERVICES IN SUPPORTING PHYSIOTHERAPY INTERVENTIONS FOR VULNERABLE POPULATIONS. - 1Naif Ali Mohammed Ali, 2Mahboob AaliManea Allah Alharbi, 3Walaa Mohammed MoiedKhawaji, 4Saleh Mohammed Hussain Al Daghman, 5Ibrahim Azan Ali Alkhreem, 6Saleh Mohsen Algareh, 7Hadi Hamad Al Oqiel (Chelonian Research Foundation, 2023)
This article critically examines the role of social administration in advancing physiotherapy for distraught bunches. It investigates the association between social and physical wellbeing and emphasizes the significance of collective activity to meet the wants of marginalized groups. This article examines vital discoveries, counting the effects of well-being decision-making, the role of well-being care in advancing physiotherapy, and issues confronting the current restorative framework. The suggestions are planned to energize collaboration between social services and physiotherapists to move forward the wellbeing of individuals with disabilities. Keywords: physiotherapy, social services, vulnerable populations, healthcare, social determinants of health